Cooperatives for Sustainable Economic Development: A Case of Chandrapur Pashupalan Saving and Credit Cooperative Ltd. Surkhet, Nepal - Dhakal, Aishwarya Prashad (NPRC Journal of Multidisciplinary Research, 2024)
This paper discusses the economic development through cooperative as initiated in a Chandrapur village of Surkhet District, Nepal. This is a case study of a saving and credit co-operative projected towards promoting animal husbandry in the rural area of Nepal. To analyze the economic empowerment of cooperative members of saving and credit cooperative was set as the study objective. This study is primarily marked with the descriptive research design followed with qualitative data and information collected from the field and described and analyzed in the text of this paper. Findings of the study show that the cooperatives in the rural areas are functioning more smoothly than the urban areas. This Chandrapur Animal Husbandry Saving and Credit Cooperative has carried out the better success than the previous years since its establishment of the structure, functioning and its meaning in the context of local people's view have been considered as a sustainable venture operating in their area.